2023
DOI: 10.1136/bmjopen-2022-070253
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal prehabilitation for major surgery in elderly patients to lower complications: protocol of a randomised, prospective, multicentre, multidisciplinary trial (PREHABIL Trial)

Abstract: IntroductionThe global volume of surgery is growing and the population ageing, and economic pressure is rising. Major surgery is associated with relevant morbidity and mortality. Postoperative reduction in physiological and functional capacity is especially marked in the elderly, multimorbid patient with low fitness level, sarcopenia and malnutrition. Interventions aiming to optimise the patient prior to surgery (prehabilitation) may reduce postoperative complications and consequently reduce health costs.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Moreover, digitalization would help lower the impact of staff and facility shortage. There are ongoing trials aiming to prove the clinical-as well as the cost-effectiveness of such programs [24][25][26][27]. Community based prehabilitation has also been proven to reduce postoperative complications [28], the cost-effectiveness of this type of programs is to be analysed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, digitalization would help lower the impact of staff and facility shortage. There are ongoing trials aiming to prove the clinical-as well as the cost-effectiveness of such programs [24][25][26][27]. Community based prehabilitation has also been proven to reduce postoperative complications [28], the cost-effectiveness of this type of programs is to be analysed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of nutritional status was insufficient and, as in our cohort, no patient received nutritional supplementation. Structured, multimodal prehabilitation protocols that include respiratory therapy and protein supplementation demonstrate a positive impact on preoperative physiological reserve with sustainable levels of functional capacity after surgery [ 14 ]. First, the rehabilitation approach was made by our nurses usually on the day before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lenght of stay, days -mean (min-max) 13 (4-67)ICU admission -n (%) 5 (5%) Time to first bowel movement, days -mean (min-max) 3 (0-7)Time to solid oral intake, days -mean (min-max) 6(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) …”
mentioning
confidence: 99%
“…A recent pooled analysis confirmed that nutritional status influences the efficiency of a 4-week multimodal prehabilitation in colorectal cancer surgery [ 45 ]. Thus, prehabilitation is very likely to benefit mostly malnourished patients, which are at higher risk of postoperative complications [ 46 , 47 , 48 ]. Secondly, the reviewed studies focused on a wide variety of surgical interventions.…”
Section: Discussionmentioning
confidence: 99%